'Make money, get money': how two autonomous schools have commercialised their services. Issue 6 (2nd November 2019) - Holloway, Jessica; Keddie, Amanda
ABSTRACT: Using the stories of two autonomous public schools in Australia, this paper demonstrates how commercialisation can simultaneously position schools as both consumer and for-profit producer. Drawing on Foucault's articulation of discourse as that which constitutes and makes available what is possible to be said, done and imagined, the paper illustrates how the current marketised articulation of education is allowing for new possibilities of commercialisation in schools. Together these stories demonstrate that there are creative ways that these schools have embraced their autonomy, while relying on market solutions to acquire the resources they deem necessary for their students and their communities. However, it also shows how these resources and the attainment for them are inextricably constituted by the market orientation of education more broadly and how this presents potential dangers for what schools may be and become as a result.